Analisis Bahasa dan Nilai Puisi “Basa Bali” Oleh Suntari Pr. - Astuti, Ida Ayu Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Balinese poem entitled Basa Bali, created by Suntari Pr in 1959, was a milestone in the birth of modern Balinese poetry. This poem is full of values ​​and meaning, both implicitly and explicitly. This research aims to describe the form and translation, language studies and values ​​of Basa Balinese poetry. This research uses a qualitative approach. The data source comes from Balinese poetry entitled Basa Bali which was obtained through literature study which was then analyzed to obtain data presented in descriptive form. The results of this research are that Balinese basa poetry uses Balinese alus, free rhythm, uses five metaphors and uses Balinese language objects as symbolism. The values ​​contained in this poetry include moral values, social values, cultural values ​​and religious values.